Validation of hair type diversification for recruiting shampoo panelists without losing data relevance. (7th September 2020) - Tabary, C.; Pouradier, F.; Belkebla, S.; Panhard, S.; Carvalho, L.; Vincenzi, F.
Abstract: A sensory descriptive method is used by the industries to characterize their various products under development. The sensory panelists are recruited through some general criteria suggested in International Standard Sensory Analysis – General guidelines for the selection, training and monitoring of selected assessors and expert sensory assessors [5] but for hair product evaluation, some hair criteria should also be considered, as a major challenge lied in the difficulty to recruit panelists. Such an issue led us to find practical solutions to make this recruitment easier. Among others, one possible solution was to restrict some requirements in the characteristics of hair. This study aimed at checking if a hair type diversification on either sensitization or curliness could influence the sensory perception of shampoos, and, if so, to which extent. This study demonstrates that, for a shampoo trained panel, the evaluation is impacted by the hair curliness but is not impacted by the hair sensitization level. Résumé: Une méthode de description des sensations est utilisée par les industries pour caractériser leurs différents produits en cours de développement. Des membres sont recrutés pour un panel en se basant sur certains critères généraux suggérés dans la Norme Internationale d'Analyse sensorielle – Directives générales pour la sélection, la formation et la supervision des évaluateurs sélectionnés et des évaluateurs sensoriels experts [5], mais pour l'évaluation des cheveux, certains critères doivent également être pris en compte, car une des principales difficultés consiste à recruter des panélistes. Ce problème nous a obligé de trouver des solutions pratiques pour faciliter ce recrutement. Entre autres, une solution possible était de limiter certaines exigences au niveau des caractéristiques des cheveux. Cette étude vise à vérifier si la diversité au niveau de la sensibilité ou de la frisure de la chevelure pourrait influencer la perception sensorielle des shampooings, et, si c'est le cas, dans quelle mesure. Cette étude démontre que, pour une palette de 6 shampooings développés, l'évaluation est impactée par la frisure de la chevelure7mais n'est pas impactée par le niveau de sensibilité.